Problematika Guru Dalam Pemanfaatan Media Pembelajaran - Sihombing, Yenni; Haloho, Bongguk; Napitu, Ulung (JUPE : Jurnal Pendidikan Mandala, 2023)
Abstract. Revolutions in science and technology, changes in society, understanding how children learn, advances in communication and information media and so on give their own meaning to educational activities. This challenge is one of the important foundations of a technological approach in the management of education and learning. The development of science and technology is increasingly encouraging renewal efforts in the utilization of technological results in the learning process. Teachers are required to be able to use the tools that can be provided by the school, and it is possible that these tools are in accordance with the developments and demands of the times. Utilization of learning media is also a must for every teacher so that it helps in clarifying learning material and arousing students' interest and motivation in learning. However, in reality there are still many teachers who have not been able to utilize learning media, teachers are also less innovative and creative in using learning media, meaning that teachers cannot work in using learning media.Keywords: Teacher Problems; Utilization of Learning Media  Abstrak. Revolusi ilmu pengetahuan dan teknologi, perubahan masyarakat, pemahaman cara belajar anak, kemajuan media komunikasi dan informasi dan lain sebagainya memberi arti tersendiri bagi kegiatan pendidikan. Tantangan tersebut menjadi salah satu dasar pentingnya pendekatan teknologis dalam pengelolaan pendidikan dan pembelajaran.  Perkembangan ilmu pengetahuan dan teknologi semakin mendorong upaya -upaya pembaharuan dalam pemanfaatan hasil-hasil teknologi dalam proses belajar. Para guru dituntut agar mampu menggunakan alat-alat yang dapat disediakan oleh pihak sekolah, dan tidak menutup kemungkinan bahwa alat-alat tersebut sesuai dengan perkembangan dan tuntutan zaman.  Pemanfaatan  media pembelajaran juga merupakan suatu keharusan bagi setiap guru sehingga membantu dalam memperjelas materi pembelajaran dan membangkitkan minat dan motivasi siswa dalam belajar. Namun pada kenyataannya masih banyak guru yang belum mampu untuk memanfaatkan media pembelajaran, guru juga kurang inovatif dan kreatif dalam pemanfaatan media pembelajaran artinya guru belum bisa bekerja dalam menggunakan media pembelajaran.Kata Kunci : Masalah Guru; Pemanfaatan Media Pembelajaran.